2015
DOI: 10.19159/tutad.37050
|View full text |Cite
|
Sign up to set email alerts
|

Diyarbakır İli Silvan İlçesi Taban Meralarının Vejetasyon Yapısı Üzerinde Bir Araştırma

Abstract: Özet: Bu araştırma, Diyarbakır ili Silvan ilçesinin taban kesimindeki 6 farklı merada, vejetasyon yapısının belirlenmesi amacıyla 2014 yılında yürütülmüştür. Araştırmada, her merada toplam 4 lup hattındaki 400 noktada ölçüm yapılarak meradaki bitkilerin türleri, cins ve familyaları, etkileri (azalıcı, çoğalıcı, istilacı), ömür uzunlukları, meraların bitki ile kaplı alan oranları ve türlerin botanik kompozisyondaki oranları saptanmıştır. Yapılan vejetasyon etütlerinde, 11 familyadan, 35 cinse ait toplam 43 türe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In the previous studies in Turkey, rangeland area rate covered with plants was 60.55% in Ankara province (Unal et al, 2012a), 59.1% in Diyarbakir province (Seydosoglu et al, 2015a), 88.2% in Sinop province (Alay et al, 2016), 93.57% in Bartin province (Uzun et al, 2016). These results indicate that the plant-covered area of rangelands was changed significantly due to both regional conditions and utilization methods.…”
Section: Status and Health Of Rangelandmentioning
confidence: 70%
See 2 more Smart Citations
“…In the previous studies in Turkey, rangeland area rate covered with plants was 60.55% in Ankara province (Unal et al, 2012a), 59.1% in Diyarbakir province (Seydosoglu et al, 2015a), 88.2% in Sinop province (Alay et al, 2016), 93.57% in Bartin province (Uzun et al, 2016). These results indicate that the plant-covered area of rangelands was changed significantly due to both regional conditions and utilization methods.…”
Section: Status and Health Of Rangelandmentioning
confidence: 70%
“…In general, botanical composition of rangelands form a group expressed as "other family dominant rangeland" like mentioned as Comakli et al (2012) The vast majority of the studied rangelands were occupied by invader species. In other studies conducted in different regions of Turkey, it was reported that invader species constitute the majority of rangeland vegetation (Erden et al, 1994;Aydin and Uzun, 2000;Sahinoglu, 2010;Uzun et al, 2010;Unal et al, 2011;Koc and Kadioglu, 2012;Unal et al, 2012a and2012b;Yavuz et al, 2012;Unal et al, 2013;Unal et al, 2014;Seydosoglu et al, 2015aSeydosoglu et al, , 2015bSeydosoglu et al, and 2015cUzun et al, 2016;Ispirli et al, 2016).…”
Section: Plant Speciesmentioning
confidence: 98%
See 1 more Smart Citation